Dynamic simulation and optimization of an industrial-scale absorption tower for CO2 capturing from ethane gas. (November 2016) - Pouladi, Babak; Nabipoor Hassankiadeh, Mojtaba; Behroozshad, Flor
Abstract: This article considers a process technology based on absorption for CO2 capturing of ethane gas in phase 9 and 10 of south pars in Iran using diethanolamine (DEA) as absorbent solvent. This CO2 capture plant was designed to achieve 85% CO2 recovery and obtain 19 ppm the CO2 concentration in the outlet of absorber. ASPEN–HYSYS software was used for the dynamic simulation of a commercial-scale CO2 capture plant and amine Pkg equation was chosen from the fluid property package for calculating the thermodynamic properties of the process. A static approach for optimization was used to evaluate the optimum conditions. This research revealed that pressure variation does not have any considerable changes in the absorption process, while both amine inlet temperature and volumetric flow rate increment enhance the absorption tower efficiency. The effect of temperature was very significant as shown in the dynamic study plots. The optimum condition for CO2 absorption from a stream of ethane gas with molar flow rate of 2118 kg mol h −1 was obtained 75 m 3  h −1 of amine at 53 °C and 24 bar. This optimized condition is acceptable from economical, safe as well as feasible point of view.